Fatores que influenciam ou inibem a utilização de agrotóxicos por agricultores(as) familiares do município de Itapejara d'Oeste - PR - Costa Junior, Nereu Antonio de (2024)
This study aimed to analyze the factors that influence or inhibit the use of pesticides by family farmers in Itapejara d’Oeste-PR. The research is justified by the increasing use of pesticides in Brazil, contrasting with global demands for more sustainable agricultural practices. It is an exploratory and descriptive study with a mixed approach (qualitative-quantitative), employing a case study method. Data collection involved interviews with 27 family farmers identified among 54 properties receiving public technical assistance. A semi-structured questionnaire covered topics such as agricultural practices, pesticide impacts, and natural alternatives. Data were analyzed using thematic content analysis, identifying three main categories: individual factors (economic, social, environmental, and opportunities), community relationship factors and “non-rational” motives, and governmental, institutional, or legal factors. Results indicate that pesticide use is primarily driven by economic factors, such as productivity gains and cost reductions, but is counterbalanced by concerns about human health, environmental impact, and community perceptions of more sustainable practices. Furthermore, insufficient public policies, weak enforcement, and educational gaps significantly influence this context. The study highlighted that adopting more balanced and sustainable practices is achievable through increased technical support, effective public policies, investments in education and awareness, and enhanced research and regulatory enforcement. Findings demonstrated that transitioning to sustainable agriculture not only mitigates environmental and social damages caused by indiscriminate pesticide use but also fosters economic benefits by encouraging productive diversification and access to markets for healthier products. Such strategies enable family farming to contribute to sustainable development, meeting global demands for food security without jeopardizing the health of farmers, local communities, and ecosystems.